THE CONTRIBUTION OF CONGREGATION MOTIVATION TO THE LEVEL OF ACTIVE PARTICIPATION AT THE RAHEELA YOUTH MOSQUE IN BANDUNG - Farhan, Muhammad; Wibowo , Hari Santoso; Masrukan, Fathurrahman (RADJA PUBLIKA, 2025)
This study investigates the influence of Congregation Motivation on the level of Active Participation at Raheel Youth Mosque Bandung. Active participation, crucial for mosque revitalization, was measured by engagement in worship, education, and social services. Employing a quantitative survey design with 150 active members, the study utilized Simple Linear Regression. Results indicate a strong positive correlation and significant predictive power, with Motivation explaining 61.0% of the variance in Participation (β=0.781, p<0.001). Intrinsic Motivation (spiritual rewards) was the dominant driver (Mean=4.35). These findings suggest that mosque management should prioritize programs that enhance the spiritual depth and relevance of activities to sustain high engagement. This research provides empirical evidence for strategic mosque management targeting urban youth.